Underspecified Query Refinement via Natural Language Question Generation - Sajjad, Hassan; Pantel, Patrick; Gamon, Michael (ACL/SIGPARSE, 2012)
Underspecified queries are common in vertical search engines, leading to large result sets that are difficult for users to navigate. In this paper, we show that we can automatically guide users to their target results by engaging them in a dialog consisting of well-formed binary questions mined from unstructured data. We propose a system that extracts candidate attribute-value question terms from unstructured descriptions of records in a database. These terms are then filtered using a Maximum Entropy classifier to identify those that are suitable for question formation given a user query. We then select question terms via a novel ranking function that aims to minimize the number of question turns necessary for a user to find her target result. We evaluate the quality of system-generated questions for grammaticality and refinement effectiveness. Our final system shows best results in effectiveness, percentage of well-formed questions, and percentage of answerable questions over three baseline systems.